(untitled) (SCHOOLAR: Social and Literature Study in Education, 2022)
This study discusses the implementation of the curriculum in improving the quality of graduates which is motivated by the importance of the curriculum to education. This study aims to: 1) describe curriculum planning in improving the quality of MAPK graduates at MAN 4 Jombang; 2) describe the implementation of the curriculum in improving the quality of MAPK graduates at MAN 4 Jombang; 3) describe the supporting and inhibiting factors of curriculum implementation in improving the quality of MAPK graduates at MAN 4 Jombang. This research uses descriptive qualitative research. Data collection techniques by means of observation, interviews, and documentation. The data obtained during the study were analyzed by means of data reduction, data presentation, and drawing conclusions. The results of the research at MAPK MAN 4 Jombang are: 1) Curriculum planning in improving the quality of graduates has been well prepared since the beginning of the school year; 2) curriculum implementation in improving the quality of graduates consists of the readiness of learning tools (RPP and Syllabus) before the learning process, MAPK MAN 4 Dormitory with complete facilities; 3) supporting factors for curriculum implementation in improving the quality of graduates are adequate infrastructure, teacher readiness in teaching, and the disciplined attitude of madrasa residents. In addition, the inhibiting factor for implementing the curriculum in improving the quality of graduates is the number of outside activities that interfere with the learning process.